Students' perceptions on the Use of Paralanguage in EFL Classrooms - Kok, Alfian Sandy William; Misa, Mikhael; Bouk, Edmundus; Seran, Yanuarius (International Journal of English Education and Linguistics (IJoEEL), 2025)
This study examined students’ perceptions of English language teachers’ use of paralanguage in schools on the border between Indonesia and Timor Leste, specifically examining its impact on students’ engagement and comprehension in an English as a Foreign Language (EFL) environment. Paralanguage—encompassing vocal qualities such as pitch, pitch, volume, and rate of speech—plays a critical yet often overlooked role in effective communication, especially in a language learning environment where non-verbal cues can significantly impact students’ comprehension. Through qualitative methods, including observation and semi-structured interviews with students at SMA Fides Quarens Intellectum and SMA Negeri 2 Kefamenanu, this study investigated how students interpreted their teachers’ paralinguistic cues and how these cues influenced their learning experiences. The findings revealed that students perceived paralanguage as a valuable tool for enhancing clarity and emotional connection in the classroom, aiding their comprehension and encouraging active participation. Elements such as pitch modulation and vocal emphasis were shown to help students understand important information and stay engaged, while balanced vocal qualities created a supportive and engaging classroom atmosphere. Furthermore, this study highlights the role of paralanguage in reducing student anxiety and increasing self-confidence, which is particularly relevant in cross-cultural educational settings where language barriers and cultural differences can hinder effective communication. These insights underscore the importance of incorporating paralanguage awareness into teacher training programs, suggesting that the intentional use of vocal cues can enhance instructional effectiveness and support student language acquisition.